2015
DOI: 10.1136/tobaccocontrol-2014-051906
|View full text |Cite
|
Sign up to set email alerts
|

The allure of the waterpipe: a narrative review of factors affecting the epidemic rise in waterpipe smoking among young persons globally

Abstract: ObjectiveThe objective of this narrative review is to highlight the determinants of the epidemic rise in waterpipe tobacco smoking (WTS) among youth globally. The Ecological Model of Health Promotion (EMHP) was the guiding framework for the review.Data sourcesThe following electronic databases were searched: Cochrane library, MEDLINE, EMBASE, PsycINFO, Web of Science and CINAHL Plus with Full Text. Search terms included waterpipe and its many variant terms.Study selectionArticles were included if they were pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(183 citation statements)
references
References 161 publications
(178 reference statements)
10
172
0
1
Order By: Relevance
“…Responses could include multiple themes so counts within these groups are not mutually exclusive. Participants' responses to the closed-ended items are consistent with research indicating young adults do not perceive WTS to be addictive and believe they can easily quit 21 . Although research indicates WTS is influenced by a number of factors, such as social use and product features like appealing flavorings, studies have consistently shown that such WTS perceptions are associated with waterpipe tobacco initiation and current use [54][55][56][57][58][59] .…”
Section: Open-ended Responsessupporting
confidence: 60%
See 3 more Smart Citations
“…Responses could include multiple themes so counts within these groups are not mutually exclusive. Participants' responses to the closed-ended items are consistent with research indicating young adults do not perceive WTS to be addictive and believe they can easily quit 21 . Although research indicates WTS is influenced by a number of factors, such as social use and product features like appealing flavorings, studies have consistently shown that such WTS perceptions are associated with waterpipe tobacco initiation and current use [54][55][56][57][58][59] .…”
Section: Open-ended Responsessupporting
confidence: 60%
“…Open-ended items. Open-ended questions were developed for this study based on prior research on waterpipe tobacco use behavior, perceptions, and addiction 13,20,21 . These questions probed at perceptions of the addictiveness of WTS, thoughts on what it means to be addicted to WTS, and feedback on what message content may be effective to convey the addictiveness of WTS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the few studies on adolescents, most, if not all, have been based on Western (e.g., Canada, the US and UK) or Middle East populations (Akl et al 2015;Zyoud et al 2014). Cigarette smoking is the most important predictor of waterpipe use among adolescents (Barnett et al 2009;Jawad et al 2015a, b;Minaker et al 2015;Palamar et al 2014;Smith et al 2011;Weglicki et al 2008).…”
Section: Introductionmentioning
confidence: 99%